Pre-service EFL Teachers' Readiness for Using ICT-based Media in Listening: A Survey on Higher Education Students - Zhafira, Zahra; Rizal, Daviq (Universitas Islam Negeri Raden Intan Lampung, 2024)
With the increasing influence of technology in education, it is critical to comprehend how prepared future educators are to employ ICT technologies for language instruction. This research aims to determine the level to which pre-service English as a Foreign Language (EFL) teachers are prepared to use media based on information and communication technology (ICT) in the context of listening skills development. The research focuses on higher education students pursuing EFL teacher training programs and looks at how they use ICT-based media to shed light on their attitudes, skills, and perceived barriers. This study employs a descriptive quantitative research method, utilizing a questionnaire to assess the preparedness of 100 pre-service EFL teachers for using ICT-based media in language learning, particularly in listening classes, with data analyzed through charts and narrative explanations. The results of this study are expected to add to the existing knowledge regarding the use of technology in language teaching. Furthermore, this study can offer useful suggestions for integrating ICT-based media into improving listening abilities and encouraging more efficient and interesting language learning environments in EFL classrooms